Vaping Exacerbates Coronavirus-Related Pulmonary Infection in a Murine Model - Sivaraman, Vijay; Parker, De’Jana; Zhang, Rui; Jones, Myles M.; Onyenwoke, Rob U. (Frontiers in Physiology, 2021)
Though the current preponderance of evidence indicates the toxicity associated with the smoking of tobacco products through conventional means, less is known about the role of “vaping” in respiratory disease. “Vaping” is described as the use of electronic cigarettes (E-Cigarettes or E-Cigs), has only more recently been available to the public ( 10 yrs) but has quickly emerged as a popular means of tobacco consumption worldwide. The World Health Organization (WHO) declared the SARS-CoV-2 outbreak as a global pandemic in March 2020. SARS-CoV-2 can easily be transmitted between people in close proximity through direct contact or respiratory droplets to develop coronavirus infectious disease 2019 (COVID-19). Symptoms of COVID-19 range from a mild flu-like illness with high fever to severe respiratory distress syndrome and death. The risk factors for increased disease severity remain unclear. Herein, we utilize a murine-tropic coronavirus (beta coronavirus) MHV-A59 along with a mouse model and measures of pathology (lung weight/dry ratios and histopathology) and inflammation (ELISAs and cytokine array panels) to examine whether vaping may exacerbate the pulmonary disease severity of coronavirus disease. While vaping alone did result in some noted pathology, mice exposed with intranasal vaped e-liquid suffered more severe mortality due to pulmonary inflammation than controls when exposed to coronavirus infection. Our data suggest a role for vaping in increased coronavirus pulmonary disease in a mouse model. Further, our data indicate that disease exacerbation may involve calcium (Ca2+) dysregulation, identifying a potential therapeutic intervention.